ANALISIS PENGENDALIAN KUALITAS PROSES PENGANTONGAN SEMEN - Sulistyarini, Dwi Hadi; Cahyawati, Amanda Nur (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
PT. Semen Indonesia (Persero), Tbk is a leading cement producer. So the need to apply a good quality control system on all of its products and service to customers throughout the process. One was in the process of packing cement in Section Finish Mill and Packer Operation. However, nobody can deny there are problems with the quality of the assembled packing cement in Section Finish Mill and Packer Operation. One of them is the rupture of the cement bags when filled. This research was conducted using six sigma method. Data from six sigma analyzed by the controller quality Statistics or Statistical Process Control (SPC). Fishbone diagram based on the obtained information that the machine (conveyor) and the human operator is an aspectl that must be repaired. Improvement recommendations given are to increase alertness operator during the filling process takes place and gives the opponent's pockets and double-check the bag to be used.